On ϕ-Symmetric N(k)-Paracontact Metric Manifolds - D. G. Prakasha; K. K. Mirji (Journal of Mathematics)
The notions of ϕ-symmetric, 3-dimensional locally ϕ-symmetric, ϕ-Ricci symmetric, and 3-dimensional locally ϕ-Ricci symmetric N(k)-paracontact metric manifolds have been introduced and properties of these structures have been discussed.